2014
DOI: 10.1007/s11356-014-3510-7
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of Lens culinaris with Pb-resistant bacteria shows potential for phytostabilization

Abstract: Phytoremediation comprises a set of plant and microbe-based technologies for remediation of soil heavy metal contamination. In this work, four Pb-resistant bacteria (Agrobacterium tumefaciens, Rahnella aquatilis, and two Pseudomonas sp.) were selected among a collection of isolates from root nodule of Lens culinaris. They had a high degree of bioaccumulation ability in nutrient medium containing 2 mM Pb, and the maximum Pb accumulation of whole cell was found after 48-h incubation. These Pb-resistant bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…This research revealed that the inoculation of Lathyrus sativus with efficient and resistant PGPR (I4 consortium) has markedly affected plants growth under lead stress (0.5 mM Pb), thus significantly increased the dry biomass of whole plant, as compared to uninoculated plants. These measurements are in agreement with the previous experiments which confirmed the effective role of combined inoculations of PGPR in stimulating shoot and root biomasses of different legumes under heavy metals stress [46,57,58]. Saadani et al [8] also confirmed the beneficial effect of co-inoculation with PGPR on growth of Vicia faba, Lens culinaris, and Sulla coronaria when cultivated in mine tailings that contain high proportions of Pb and Zn.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This research revealed that the inoculation of Lathyrus sativus with efficient and resistant PGPR (I4 consortium) has markedly affected plants growth under lead stress (0.5 mM Pb), thus significantly increased the dry biomass of whole plant, as compared to uninoculated plants. These measurements are in agreement with the previous experiments which confirmed the effective role of combined inoculations of PGPR in stimulating shoot and root biomasses of different legumes under heavy metals stress [46,57,58]. Saadani et al [8] also confirmed the beneficial effect of co-inoculation with PGPR on growth of Vicia faba, Lens culinaris, and Sulla coronaria when cultivated in mine tailings that contain high proportions of Pb and Zn.…”
Section: Discussionsupporting
confidence: 89%
“…The bioaccumulation results showed that the potential to enhance Pb 2+ retention in selected PGPR was not only due to cell‐surface binding, but also to intracellular accumulation as also observed by Jebara et al . The most part of Pb 2+ was adsorbed to cell surface of all bacteria .…”
Section: Discussionsupporting
confidence: 70%
“…According to these results, the potential to enhance Pb 2+ retention in the selected PGPR was not only due to cell-surface binding, but it also was due to intracellular accumulation [25]. Similar results have also been reported by Jebara et al (2015) [26], denoting that PGPR microorganisms may reduce soil pH and increase soil Pb availability through releasing organic acids (e.g., carboxylic acid) [27].…”
Section: Resultssupporting
confidence: 83%
“…Similarly, co-inoculation of lentil with Pb-resistant bacteria (A. tumefaciens, R. aquatilis, and Pseudomonas sp.) increases CAT, SOD, and POD activities in plants under Pb stress [42]. An endophytic fungus (EF0801) benefits rice growth under moderate Pb stress by enhancing CAT, SOD, and POD and reducing MDA levels [12].…”
Section: Lead Bioavailability In Soil and Pb Accumulation And Uptake mentioning
confidence: 99%